Decadence and Japan - Evangelista, S-M; Desmarais, J; Weir, D (Oxford University Press, 2021)
In the second half of the nineteenth century, literary decadence developed in parallel with japonisme, the taste for Japanese art and culture that seized Western countries following Japan’s opening to foreign trade. This article starts with an analysis of how the intertwining of japonisme and art for art’s sake pioneered by visual artists influenced writers associated with decadence, such as Walter Pater, Arthur Symons, and Oscar Wilde. The evolving relationship between decadence and japonisme assumed a distinctive character in the work of Lafcadio Hearn, who lived in Japan all through the 1890s and wrote a series of influential books about the country. The article closes with an account of how ideas of decadence traveled back to Japan. Yōshū Chikanobu’s color prints reverse the orientalist gaze of Western artists by documenting a Japanese fascination with European culture that traditionalists viewed as a symptom of decadence. As Japanese literature opened itself to cosmopolitan influences, key writers such as Natsume Sōseki, Tanizaki Junichirō, and Mishima Yukio borrowed from Western literatures to provide ambivalent depictions of Japan’s social and cultural changes.